2015
DOI: 10.4238/2015.august.14.25
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphisms of X-ray repair cross-complementing protein 4 gene and development of pancreatic cancer

Abstract: ABSTRACT. We performed a study to evaluate X-ray repair crosscomplementing protein 4 (XRCC4) gene polymorphisms and the development of pancreatic cancer. A case-control study including 206 patients with newly diagnosed primary pancreatic cancer and 412 controls was performed between January 2011 and October 2013 in a Chinese population. Genotypes of XRCC4 rs1805377, rs2075685, rs2075686 and rs1056503 were determined using polymerase chain reaction combined with a restriction fragment length polymorphism assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The splicing impact of XRCC4 rs1805377 has been noted previously (Nalla and Rogan, 2005). This SNP has been implicated with an increased risk of gastric cancer (Chiu et al, 2008), pancreatic cancer (Ding and Li, 2015) and glioma (Zhao et al, 2013b). Similarly, the potential impact of rs1893592 in UBASH3A has been recognized (Kim et al, 2015) and is associated with arthritis (Liu et al, 2017) and type 1 diabetes (Ge and Concannon, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…The splicing impact of XRCC4 rs1805377 has been noted previously (Nalla and Rogan, 2005). This SNP has been implicated with an increased risk of gastric cancer (Chiu et al, 2008), pancreatic cancer (Ding and Li, 2015) and glioma (Zhao et al, 2013b). Similarly, the potential impact of rs1893592 in UBASH3A has been recognized (Kim et al, 2015) and is associated with arthritis (Liu et al, 2017) and type 1 diabetes (Ge and Concannon, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…The pathogenesis of pancreatic cancer involves many environmental and genetic factors, and it is reported that environmental chemicals exposure, heavy metals, and obesity contribute to the susceptibility of pancreatic cancer (Antwi et al, 2015;Kim and Ahuja, 2015;Zheng et al, 2015). Many studies have shown that genetic factors, such as E-cadherin gene, X-ray repair cross-complementing protein 4 gene, cyclooxygenase-2 gene, and DNA repair genes (Ding and Li, 2015;Shen et al, 2015;Wang et al, 2015;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The splicing impact of XRCC4 rs1805377 has been noted previously (Nalla and Rogan 2005). This SNP has been implicated with an increased risk of gastric cancer (Chiu et al 2008), pancreatic cancer (Ding and Li, 2015) and glioma (Zhao et al 2013 [b]). Similarly, the potential impact of rs1893592 in UBASH3A has been recognized (Kim et al 2015) and is associated with arthritis (Liu et al 2017) and type 1 diabetes (Ge and Concannon, 2018).…”
Section: Discussionmentioning
confidence: 99%